2016
DOI: 10.1089/end.2015.0862
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Pneumatic Cystolithotripsy: A Novel Approach

Abstract: The transurethral ureteroscopic pneumatic cystolithotripsy procedure is a safe technique for the management of large bladder calculi. It allows the bladder to collapse over the stone, leading to stone immobilization and, subsequently, decreasing lithotripsy duration. Our procedure is associated with a minimal chance of postoperative urethral injury because all stone fragments are evacuated through the cystoscope sheath, without contact with the urethral urothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
2
8
1
Order By: Relevance
“…It is the widest and most dilatable part of the entire urethra [8][9][10] • Membranous urethra; it extends from the apex of the prostate through the pelvic floor musculature until it joins the bulbous urethra. It is the narrowest part of the urethra.…”
mentioning
confidence: 99%
“…It is the widest and most dilatable part of the entire urethra [8][9][10] • Membranous urethra; it extends from the apex of the prostate through the pelvic floor musculature until it joins the bulbous urethra. It is the narrowest part of the urethra.…”
mentioning
confidence: 99%
“…Patients underwent follow-up for 18 months postoperatively, without urethral stricture reported in any patient. Thus, the authors concluded that this technique is safe and effective [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the work of Ener et al, 10 out of 43 patients needed urethrotomy before cystolitothripsy [ 13 ]. In addition, Ali et al had to make a bladder neck incision in 6 of 53 patients [ 14 ]. These maneuvers lengthened the operation time.…”
Section: Discussionmentioning
confidence: 99%
“…One of the commonly discussed aspects concerning cystolithotripsy is the risk of urethral injury, which is caused mostly by passing the cystoscope with a stone fragment through the urethra [ 14 ]. In our technique, the widest instrument inserted via the urethra is the 19F cystoscope, and this maneuver is performed only once at the beginning of the procedure.…”
Section: Discussionmentioning
confidence: 99%